Gender, crime, and punishment - Daly, Kathleen, 1948- (Yale University Press, 1994)
Are men and women who are persecuted for similar crimes punished differently? If it is true, as is commonly assumed, that women are sentenced more leniently than men, does this tendency vary by class and race? In this book Kathleen Daly explores these issues by analyzing women's and men's cases that are routinely processed in felony courts - cases of homicide, aggravated assault, robbery, larceny, and drug offenses. Daly first presents a statistical analysis of sentencing disparity for a wide sample of cases. Then, from within this sample, she compares forty matched pairs of women and men accused and convicted of statutorily similar offenses, examining in each case the presentence investigation reports and transcripts of the remarks made in court on the day of sentencing. From these documents, Daly constructs a portrait of each defendant and a narrative for each crime, and she identifies the theory of punishment the judge used to justify the sentence imposed. She analyzes whether men and women are pulled into crime in different ways, whether their offenses are comparably serious, and whether court officials use different conceptions of justice in sentencing men and women. By providing both numerical and narrative descriptions of crime and punishment, Daly shows the inadequacies of quantitative analysis: although her statistics, like those of other studies, suggest that women are favored, her close comparison of the matched pairs indicates that gender differences are negligible when the details of the cases are taken into consideration.